Correlation Between Consumption of Protein and Vitamin C Among Children Aged 12-24 Months with Anemia in the South Sumedang District - Elba, Fardila; Daryant, Eneng; Gumilang, Lani; Nurjannah, Triastika Ayu; Effendy, Nurlaela (KnE Life Sciences, 2021)
Anemia commonly occurs in infants aged 12-24 months. One of the causes of anemia in infants is a lack of vitamin C and protein. This study aimed to determine the correlation between protein intake and vitamin C on the incidence of anemia in children under 12-24 months. This research uses an analytic study design with a cross-sectional design. Randomization was conducted to obtain a study sample consisting of 96 toddlers aged 12-24 months. The instrument uses FFQ (Food Frequency Questionnaire) with bivariate (chi-square) and multivariate (multiple logistic regression) analysis. The univariate study results showed that out of 96 toddlers, 42 had anemia 42 (43.8%) and 54 did not (56.3%). Based on the bivariate test results, it was found that protein intake of the fulfilled hemoglobin levels had anemia 14.8% and those that were fulfilled did not experience anemia 85.2% with the result p = 0.000. Based on the fulfilled vitamin C intake, 18.9% anemia was fulfilled but 81.1% did not experience anemia with the result p = 0.001. Based on the multivariate test, protein intake was not fulfilled and had anemia p = 0.001, OR = 15.01. This study concludes that there is a relationship between protein and vitamin C intake on the incidence of anemia in infants, and protein intake that is not met will experience a 15x more significant influence on the incidence of anemia in infants Keywords: Children under five, Anemia, Protein intake, Vitamin C intake